The Lane - Emden Fractional Homogeneous Differential Equation - Milici, Constantin; Drăgănescu, Gheorghe (Journal of Applied Nonlinear Dynamics, 2026)
In this paper we introduce a nonlinear fractional differential equation of Lane-Emden type. We establish a solution which satisfies the Müntz-Szász theorem conditions in terms of power series. Particular solutions are established for different values of the parameters. A validation of our method is based on a case verified with the aid of a Maple program.